Effects of sled towing on sprint starts - Cottle, C. A.; Carlson, L. A.; Lawrence, M. A. (The Journal of Strength and Conditioning Research, 2014)
Sled towing is a popular method of sprint training. Researchers have struggled to identify a loading scheme that is most appropriate to improve sprint performance in the acceleration phase. The purpose of this study was to determine if loads of 10% body weight (BWT) or 20% BWT produced significantly greater propulsive ground reaction force (GRF) impulse, peak propulsive GRF, or a greater propulsive rate of force development (RFD) than an unweighted sprint start. Seventeen healthy court and field athletes (10 men, 7 women; 20.9 ± 1.1 years) completed 5 starts of each condition (unweighted, 10% BWT, 20% BWT). Participants began each start in an upright staggered stance. Propulsive GRF impulse was greater in the 20% BWT condition than the unweighted condition in both limbs and greater in the 20% BWT condition than the 10% BWT condition in the front leg only, and vertical GRF impulse was greater in the 20% BWT than the unweighted condition. In summary, our results suggest that a 10% BWT load is not sufficient to increase propulsive GRF impulse. A loading scheme of 20% BWT is sufficient to increase propulsive GRF impulse. Coaches seeking to improve sprint starts may observe improvements using a load of 20% BWT during training while towing a sled.